Erratum: "Development, Validation and Approbation Analytical Method for the Quantitative Determination of Taurine by HPLC-UV Method in the Test of Comparative Dissolution Kinetics" - A. M. Poluyanov; A. Kochug; L. S. Mitrofanova; I. D. Nikitin; O. Yu. Vergasov; I. E. Shohin (Разработка и регистрация лекарственных средств, 2023)
Drug development & registration. 2023;12(2):62–72. (In Russ.) https://doi.org/10.33380/2305-2066-2023-12-2-62-72. Published: 25.05.2023.